2022
DOI: 10.1371/journal.pone.0265838
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PCSK9 inhibition with evolocumab on lipoprotein subfractions in familial dysbetalipoproteinemia (type III hyperlipidemia)

Abstract: Background and aims Familial dysbetalipoproteinemia (FDBL) is a rare inborn lipid disorder characterized by the formation of abnormal triglyceride- and cholesterol-rich lipoproteins (remnant particles). Patients with FDBL have a high risk for atherosclerotic disease. The effect of PCSK9 inhibition on lipoproteins and its subfractions has not been evaluated in FDBL. Methods Three patients (65±7 years, 23±3 kg/m2, 2 females) with FDBL (diagnosed by isoelectrofocusing) and atherosclerosis (coronary and/or cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…A small observational non-randomized and unblinded study showed a reduction of 42% in fasting non-HDL-C and 44% in VLDL-C after PCSK9 mAbs for 12 weeks in 3 patients with FD. 29 This is line with our findings showing that PCSK9 mAbs are able to lower atherogenic lipids and lipoproteins in FD.…”
Section: Discussionsupporting
confidence: 91%
“…A small observational non-randomized and unblinded study showed a reduction of 42% in fasting non-HDL-C and 44% in VLDL-C after PCSK9 mAbs for 12 weeks in 3 patients with FD. 29 This is line with our findings showing that PCSK9 mAbs are able to lower atherogenic lipids and lipoproteins in FD.…”
Section: Discussionsupporting
confidence: 91%
“… 46 Therefore, PCSK9-inhibiting interventions are being employed to drastically reduce plasma LDL levels. 47 …”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 acts as a catalyst and directs the endocytosis and lysosomal degradation of LDLR, hence decreasing LDLR recycling and its involvement in clearing plasma LDL . Therefore, PCSK9-inhibiting interventions are being employed to drastically reduce plasma LDL levels …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the effect of lipid ratios and TGGi was higher among patients who had cholesterol remnants above 30 mg/dl. A report of three patients with familial dysbetalipoproteinemia (type III hyperlipidemia), an uncommon form of mixed hyperlipidemia characterized by the accumulation of triglyceride‐ and cholesterol remnants, PCSK9 inhibition reduced VLDL‐cholesterol and the concentration of apoB containing lipoproteins throughout the whole density spectrum 31 ; interestingly, Lipoprotein(a) was decreased in all patient groups to a similar extent. Cholesterol remnants are not a recommended treatment target and no clinical trial has evaluated the outcomes related to their reduction but our results, at least, demonstrate an additional benefit of PCSK9 inhibitors.…”
Section: Discussionmentioning
confidence: 99%